Designing a Website-Based Book Sales Information System. - Cahyani, Salsih (International Journal of Education, Information Technology, and Others, 2024)
Information and Communication Technology has such a big influence in the business world. With the development of technology, it can facilitate various activities that occur in business, such as sales transaction activities and monitoring of available merchandise stocks. This is done as an effort to determine the progress of a business. One of the technological developments that are very trending in the business world is the use of websites, such as e-commerce. To design an information system, a UML design is needed to analyze what is needed and what will be built from the system. With this UML modeling can make the process of developing a system more systematic.